Patellofemoral pain in athletes: clinical perspectives - Halabchi F; Abolhasani M; Mirshahi M; Alizadeh Z (Dove Medical Press, 2017)
Farzin Halabchi,1,2 Maryam Abolhasani,1,2 Maryam Mirshahi,1,2 Zahra Alizadeh1,2 1Sports Medicine Research Center, Neuroscience Institute, Tehran University of Medical Sciences, Tehran, Iran; 2Department of Sports and Exercise Medicine, Tehran University of Medical Sciences, Tehran, Iran Abstract: Patellofemoral pain (PFP) is a very common problem in athletes who participate in jumping, cutting and pivoting sports. Several risk factors may play a part in the pathogenesis of PFP. Overuse, trauma and intrinsic risk factors are particularly important among athletes. Physical examination has a key role in PFP diagnosis. Furthermore, common risk factors should be investigated, such as hip muscle dysfunction, poor core muscle endurance, muscular tightness, excessive foot pronation and patellar malalignment. Imaging is seldom needed in special cases. Many possible interventions are recommended for PFP management. Due to the multifactorial nature of PFP, the clinical approach should be individualized, and the contribution of different factors should be considered and managed accordingly. In most cases, activity modification and rehabilitation should be tried before any surgical interventions. Keywords: anterior knee pain, sport, rehabilitation, runners’ knee